Orientation of Cultural Values in West Java Folklore “Si Buncir”: Cultural Representation Study - Apriliyani, N. Yeffa Afnita; Sunendar, Dadang; Syihabuddin, Syihabuddin; Sumiyadi, Sumiyadi (Jurnal Lingua Idea, 2023)
A cultural approach in folklore can be both a medium and an effective learning material. Culture contained various kinds of values that were needed as a provision for the lives of students later. This study examined the orientation of cultural values contained in the folklore "Si Buncir". This study aimed to reveal and describe the essence of life, the essence of work, human perception of time, views of nature, and the relationship between humans and humans in the folklore "Si Buncir". This research used the descriptive analysis method within the scope of literary research with reading, listening, and note-taking techniques comprehensively works using research on the orientation of cultural values in the folklore “Si Buncir”. The amount of data analyzed was 36 data in the story "The Buncir". This study's results showed that the essence of life in the story could be good or bad, but the characters in this story fight for and strive for a good life. The essence of the work in the story was not only to provide for or earn money for survival but also position and prestige. Human perception of time in the story showed more orientation to the future. The view of nature in the story was excellent, whereas the community or the characters treat nature well in this story. The relationship between humans and humans in the story showed a horizontal direction where the characters show an attitude of mutual acceptance. The implication of this research was that the value of folklore and the culture contained there in was a characteristic of culture in West Java in general. Folklore can be developed into interesting literature teaching materials for students that can be adapted to the age of the child.